2020
DOI: 10.1080/07391102.2020.1817788
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of exfoliated multilayer graphene and its putative interactions with SARS-CoV-2 virus investigated through computational studies

Abstract: Our work investigates the interaction of synthesized graphene with the SARS-CoV-2 virus using molecular docking and molecular dynamics (MD) simulation method. The layer dependent inhibitory effect of graphene nanosheets on spike receptor-binding domain of 6LZG, complexed with host receptor i.e. angiotensin-converting enzyme 2 (ACE2) of SARS-CoV-2 was investigated through computational study. Graphene sample was synthesized using mechanical exfoliation with shear stress and its mechanism of inhibition towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that it is suitable to dock the GN (with a small size) to the proteins using AutoDock Vina. 45,53,54 AutoDock Vina can provide the docking score and the root-mean-square deviation (RMSD). The docking score indicates the affinity between the receptor and the ligand, and the RMSD represents the difference in the position of the ligand from the best model.…”
Section: ■ Model and Methodsmentioning
confidence: 99%
“…Previous studies have shown that it is suitable to dock the GN (with a small size) to the proteins using AutoDock Vina. 45,53,54 AutoDock Vina can provide the docking score and the root-mean-square deviation (RMSD). The docking score indicates the affinity between the receptor and the ligand, and the RMSD represents the difference in the position of the ligand from the best model.…”
Section: ■ Model and Methodsmentioning
confidence: 99%
“…Graphene, a material with antimicrobial and antiviral properties, has increased the interest of the scientific community in investigating its use in preventive measures, detection, and diagnosis of COVID-19 (Damiati et al, 2021;Mojsoska et al, 2021;Payandehpeyman et al, 2021;Pinals et al, 2021;Raval et al, 2020;Torrente-Rodríguez et al, 2020). Graphene-based face masks are newly developed biocompatible medicinal weapons that seem worthy of facing the COVID-19 pandemic.…”
Section: Recent Advances In Graphene-based Face Masks and Benefitsmentioning
confidence: 99%
“…This electronic movement destroyed the lipid membrane, generated highly reactive species, and reduction in metabolism, which finally degrade the glutathione and virus. For instance, a computational study demonstrated an efficient binding mechanism between mechanically exfoliated multilayered graphene and the S-protein receptor binding site of SARS-CoV-2 [68] . Herein, the binding mechanism between virus and graphene flakes increased (ΔG= 28.01 Kcal/mol) as the number of layers in graphene sheets increased with edged sp 2 carbon atoms, improving catalytic surface reactivity.…”
Section: Potential Of Graphene Based Materials In Photocatalytic Viru...mentioning
confidence: 99%